SBA-Pr-SO3H: an efficient catalyst for the combinatorial synthesis of functionalized 2-aryl-4-quinazolinones using unusual γ-amino acids - Hekmat, Shohreh; Rominger, Frank (Journal of the Iranian Chemical Society, 2016)
SBA-Pr-SO3H was found as a nanocatalyst for the cyclocondensation of isatoic anhydride, aromatic aldehydes and γ-amino acids (gabapentin and baclofen) to access novel 2-aryl-4-quinazolinone γ-amino acid derivatives in solvent-free reaction conditions in good to high yields. Compared to the classical approaches, this process is a simple, highly yielding, time saving, and environmentally friendly method.Graphical abstract Open image in new window
Gesehen am 20.04.2018